Surface modification of poly(ether imide) by low-energy ion-beam irradiation and its effect on the polymer blend interface - Kim, S; Lee, KJ; Seo, Y (AMER CHEMICAL SOC, 2002)
A low-energy Ar+ ion beam was used to modify the surface Of a poly(ether imide) (PEI) powder. The modification was promoted by the oxygen gas injected during the irradiation. The surface functional groups of the modified PEI were identified with X-ray photoelectron spectroscopy (XPS). The XPS results show that the bonds. originally contained in the imide ring structure are destroyed as a result of random collisions with incident ions and energy transfer to the PEI atoms. Ion-beam irradiated PEI (IBPEI) blends with a thermotropic liquid crystalline polymer (TLCP) show more homogeneous rheological behavior than pristine PEI blends, which is attributed to an interaction between the IBPEI and the TLCP phase. Ion-beam irradiation has a strong effect on the blend morphology, the size of the dispersed phase being remarkably reduced (from 5.3 to 3 mum) and the TLCP phase being finely dispersed. Also, the adhesion between the TLCP phase and the IBPEI is definitely improved. The theoretically calculated interfacial tension of the TLCP/IBPEI blend is smaller than that of the TLCP/PEI blend, which indicates a greater interaction between the IBPEI and the TLCP phase. TLCP/IBPEI blends show more orientation (fibrillation) of the TLCP phase and better adhesion at the interface than TLCP/PEI blends do. The mechanical properties of the TLCP/IBPEI blends are improved due to the structures being more deformed and to the strong adhesion at the interface, which are correlated to the interaction between the IBPEI and the TLCP phase.
Keywords: LIQUID-CRYSTALLINE POLYMER; RHEOLOGICAL PROPERTIES; NYLON-6; POLYETHYLENE; ADHESION; BEHAVIOR